Keikutsertaan Pekebun dalam Kegiatan Konversi Tanaman Karet ke Kelapa Sawit di KUD Wisma Tani Kabupaten Rokan Hulu - Sinulingga, Muhamaad Septian Agung; Hutabarat, Sakti; Novian, Novian (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2023)
The conversion of rubber trees to oil palm is a collaborative effort by smallholders affiliated with the Wisma Tani KUD and PTPN V. The collaboration exists to help smallholders who are struggling to get funding to convert rubber plants to oil palm. The purpose of this research is to identify the characteristics of smallholders who took part in the conversion of rubber plants to oil palm at Wisma Tani KUD Rokan Hulu Regency. Understanding the extent of smallholder engagement in the implementation of rubber to oil palm conversion activities at Wisma Tani KUD Rokan Hulu Regency. Understanding the impact of smallholder characteristics on smallholder participation in the implementation of rubber to oil palm conversion operations at Wisma Tani Hulu Regency KUD Rokan. This study used cluster random sampling and was done in Hot Water Village, Pendalian IV Koto District, Rokan Hulu Regency, with a sample of 40 respondents. Descriptive statistical analysis and multiple regression analysis were employed. According to the findings of this study, smallholder participation in the planning stage is high, medium in the execution stage, high in the evaluation stage, and high in the exploitation of results. Education and land area have a substantial effect on smallholder involvement, whereas age, experience, and income have no significant effect on smallholder participation.